Can we see the invisible mind of God? (FT Press Delivers elements., 2011)
"This Element is an excerpt from Invisible forces and powerful beliefs: gravity, gods, and minds (ISBN: 9780137075454) by the Chicago Social Brain Network."--Resource description page.